2002
DOI: 10.2223/jped.901
|View full text |Cite
|
Sign up to set email alerts
|

Etiological profile of bacterial meningitis in children

Abstract: Artigo submetido em 25.06.02, aceito em 11.09.02. ResumoObjetivo: analisar o perfil etiológico e alguns aspectos epidemiológicos das crianças com meningite bacteriana, internadas em um hospital público universitário.Métodos: foram seguidas, prospectivamente, as crianças internadas com meningite bacteriana, diagnosticada segundo os critérios clínicos e laboratoriais habituais. Foram excluídos os casos de meningite pós-trauma, de meningite na vigência de derivação liquó-rica, ou de defeitos congênitos do tubo ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Of the 251 included children 129 (51.9%) had previous antibiotic treatment, result similar to that of a study done in Brasilia which observed 47.2% of children to have received an antibiotics previously [29]. This can be explain by the absence of regulation in the use of antibiotic in DR Congo were people have easy antibiotic access.…”
Section: Socio Demographic and Clinical Characteristics Of The Samplessupporting
confidence: 73%
“…Of the 251 included children 129 (51.9%) had previous antibiotic treatment, result similar to that of a study done in Brasilia which observed 47.2% of children to have received an antibiotics previously [29]. This can be explain by the absence of regulation in the use of antibiotic in DR Congo were people have easy antibiotic access.…”
Section: Socio Demographic and Clinical Characteristics Of The Samplessupporting
confidence: 73%
“…[14] In another study, about 415 children with bacterial meningitis, the causal agent was definitively identified in 69.3%: meningococcus was found in 20.6%, with a mortality of 4.6%.This same study linked a decrease in positive blood cultures, both blood and CSF, with the use of empirical antimicrobial -50.8 to 38.7% and 71.7 to 57.6%, respectively. [15] Donalisio et al [16] had positive culture in 68.7% of 568 reported cases of meningococcal disease, and suggest that age and sex did not affect the chance to confirm the diagnosis of DM by culture of CSF or blood.…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology of bacterial meningitis varies by age group and region of the world, the reasons for this association remains incompletely understood. Increased availability, awareness and usage of vaccines may contribute to change in the epidemiological pattern of these pathogens [2].…”
Section: Introductionmentioning
confidence: 99%